O perfil do líder no século XXI estudo de caso em uma instituição de ensino - Villaça, Suely Portugal (2002)
The present dissertation intended to present and to analyze the nowadays leader profile in the modern enterprise, as well as to investigate the construction of an ideal leader profile for the XXI century. Analyzing the specialized bibliography, the leader/leadership action was defined to have an essential role in the new times management, mainly in the great changes that came from the technological improvement as an globalization phenomenon consequence. At first, the classic literature about leadership was approached, making connections to the power conceptions, bureaucratized organization, productivity and the work in-group. Then, the contemporary authors postulates were approached, focusing the leadership inside the enterprises needs. Simultaneously,the work is proposed, through a case study, to consult managers and supervisors of an medium-size enterprise, intending to construct, with the proposals and considerations of the consulters, an ideal leader profile for new century. For the case study, a questionnaire was worked out and applied in a sample of forty-seven managers and supervisors of Empresa de Treinamento e Consultoria (ETC - Training and Consulting Company). After the data treatment and the construction of tables and graphs and through the results discussion, it was possible to detect the position of the personel of the related enterprise about the main attributes that are necessary to compose the nowadays enterprise leaders profile. Finally, the conclusion of the dissertation commented on the main ideas found in the literature related to leadership, emphasizing the consulters contributions,aiming the construction of a leader profile suitable to our companies